Fc-receptors as regulators of immunity. - Nimmerjahn, Falk; Ravetch, J. V. (Advances in Immunology, 2007)
Receptors for immunoglobulins [Fc-receptors (FcRs)] are widely expressed throughout the immune system. By binding to the antibody Fc-portion, they provide a link between the specificity of the adaptive immune system and the powerful effector functions triggered by innate immune effector cells. By virtue of coexpression of activating and inhibitory FcRs on the same cell, they set a threshold for immune cell activation by immune complexes (ICs). Besides their involvement in the efferent phase of an immune response, they are also important for modulating adaptive immune responses by regulating B cell and dendritic cell (DC) activation. Deletion of the inhibitory FcR leads to the loss of tolerance in the humoral immune system and the development of autoimmune disease. Uptake of ICs by FcRs on DCs and the concommitant triggering of activating and inhibitory signaling pathways will determine the strength of the initiated T-cell response. Loss of this balanced signaling results in uncontrolled responses that can lead to the damage of healthy tissues and ultimately to the initiation of autoimmune processes. In this chapter, we will discuss how coexpression of different activating and inhibitory receptors on different immune cells of the innate and adaptive immune system modulates cell activity. Moreover, we will focus on exogenous factors that can influence the balanced triggering of activating and inhibitory FcRs, such as the cytokine milieu and the role of differential antibody glycosylation.